2004
DOI: 10.1002/bit.20102
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced kinetics of genetically engineered Burkholderia cepacia: the role of vgb in the hypoxic metabolism of 2‐CBA

Abstract: Application of Vitreoscilla hemoglobin (VHb) technology to 2-CBA degradation by Burkholderia cepacia strain DNT under hypoxic conditions was studied in continuous culture chemostats. Dechlorination abilities of both recombinant (VHb gene (vgb) containing) and untransformed cells were investigated at various dilution rates to ensure complete degradation of 2-CBA. As the dilution rate increased from 0.025 to 0.25 h(-1), the ratios of chloride release to degraded 2-CBA concentration decreased from 0.95 to 0.72 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…In chemostats treating 2-CBA, strain DNT washed out from the system at a dilution rate of 0.25 day -1 while YV1 washed out from the system at 0.3 day -1 . The growth kinetics of YV1 and strain DNT also showed that plasmid maintenance produced little or no net metabolic burden on YV1 during 2-CBA degradation [Urgun-Demirtas et al, 2004]. Similar advantages of YV1 over strain DNT were also seen during the operation of the MBR system described above.…”
Section: Survival and Stability Of Recombinant Bacteria Containing Vgbsupporting
confidence: 49%
See 1 more Smart Citation
“…In chemostats treating 2-CBA, strain DNT washed out from the system at a dilution rate of 0.25 day -1 while YV1 washed out from the system at 0.3 day -1 . The growth kinetics of YV1 and strain DNT also showed that plasmid maintenance produced little or no net metabolic burden on YV1 during 2-CBA degradation [Urgun-Demirtas et al, 2004]. Similar advantages of YV1 over strain DNT were also seen during the operation of the MBR system described above.…”
Section: Survival and Stability Of Recombinant Bacteria Containing Vgbsupporting
confidence: 49%
“…Effective degradation and dechlorination of 2-CBA in continuous flow chemostats has been also demonstrated by strains DNT and YV1 at various dilution rates under hypoxic conditions [Urgun-Demirtas et al, 2004]. The percentage of the initial concentration of 2-CBA degraded decreased from 95 to 72 and from 89 to 39 for strains YV1 and DNT, respectively, as the dilution rate increased from 0.025 to 0.25 h -1 .…”
Section: Enhancement Of Biodegradation Of 2-chlorobenzoic Acidmentioning
confidence: 87%
“…HSP70 functions as a chaperone and is also known to protect cells against apoptosis (Hohfeld 1998). Hypoxic conditions represent high stress levels that can lead to the induction of genes involved in the cellular stress response such as heat shock proteins (Williams and Benjamin 2000;Ton et al 2003;van der Meer et al 2005). The relative HSP70 mRNA levels of the sibling group were upregulated under hypoxia, and that of the transgenic group did not significantly change, which also indicated that vhb transgenes in the zebrafish could partially alleviate the hypoxia stress response.…”
Section: Discussionmentioning
confidence: 98%
“…Regen SY), and petunias, overexpressing VHb can enhance the growth and survival of the plant under hypoxia stress (Dordas et al 2003;Mao et al 2003;Li et al 2005). In microbes, attempts have been made to overcome the problem of limiting oxygen by metabolically engineering bacteria to express the vhb transgene under hypoxic conditions (Patel et al 2000;Nasr et al 2001;So et al 2004;Urgun-Demirtas et al 2004). Recently, it was also suggested that VHb can improve tolerance to oxidative, nitrosative, and submergence stresses in host cells, which is based on the integration of new enzymatic functions into the host metabolic network (Kaur et al 2002;Mao et al 2003;Frey et al 2004;Li et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that expression of bacterial hemoglobin (VHb) in heterologous bacterial hosts engineered to contain the VHb gene (vgb) often results in enhancement of cell density, oxidative metabolism, protein and antibiotic production, and bioremediation, especially under oxygen-limiting conditions [17,24,35,39,40]. The beneficial effects of vgb have also been demonstrated in a variety of eukaryotes.…”
Section: Introductionmentioning
confidence: 99%